Phenology and growth of Raphia taedigera (Arecaceae) in northeastern Costa Rica wetlands. - Myers, Ronald L. (2013)
Here, I describe phenological activity of the raffia palm Raphia taedigera that dominates coastal swamps in northeastern Costa Rica. In this species, reproduction extends through the whole year, and it starts with the emergence and development of new inflorescences through the first month of the cycle. Expanded inflorescences develop into open flowers in a process that extends for three to four weeks to give rise to small fruits that are evidenced a month later. During the next twelve months or so, fruits mature but it take around six more months for all fruits to fall from the tree. Therefore, the entire reproductive process may exceed over two years. Different from other palm species, reproductive events in R. taedigera are aseasonal, and it is possible to observe palms in any reproductive state the whole year. Although the long period to fruit maturity exposes the seed to pre-dispersal losses, this disadvantage may be over weighted by the production of large and heavy seeds that mature at different times on the same inflorescence.